Circadian Misalignment of the 24-hour Profile of Endocannabinoid 2-Arachidonoylglycerol (2-AG) in Obese Adults - Hanlon, Erin C (J Clin Endocrinol Metab, 2020)
CONTEXT: The endocannabinoid (eCB) system partly controls hedonic eating, a major cause of obesity. While some studies suggested an overactivation of the eCB system in obesity, peripheral levels of eCBs across the 24-hour cycle have not been characterized in obese individuals despite the fact that in lean adults, levels of the eCB 2-arachidonoylglycerol (2-AG) vary across the day. OBJECTIVE: We sought to examine 24-hour profiles of serum concentrations of 2-AG in healthy obese and nonobese adults, under well-controlled laboratory conditions. We also simultaneously assessed 24-hour profiles of 2-oleoylglycerol (2-OG), leptin, and cortisol in each participant. DESIGN: With fixed light-dark and sleep-wake cycles, blood sampling was performed over an entire 24-hour period, including identical meals at 0900, 1400, and 1900. PARTICIPANTS: Twelve obese (8 women, mean body mass index [BMI]: 39.1 kg/m(2)) and 15 nonobese (6 women; mean BMI: 23.6 kg/m(2)) healthy adults were studied. RESULTS: We observed a 24-hour variation of 2-AG levels in obese individuals but, relative to nonobese adults, the amplitude was dampened and the timings of the nadir and peak were delayed by 4 to 5 hours. The profile of 2-OG was similarly misaligned. In contrast, when expressed relative to the 24-hour mean level, the 24-hour rhythm of cortisol and leptin were similar in obese and nonobese participants. CONCLUSIONS: Obesity appears to be associated with a dampening and delay of the 24-hour variation of eCB activity relative to the central circadian signal as well as to the daily leptin rhythm. This misalignment may play a role in the pathophysiology of obesity.